Empirical estimation of marketed surplus of rice in Bangladesh: A critical review - Jabbar, M.A. (2010)
Understanding marketed surplus and marketing behaviour of producers helps design technology, policy and institutions to facilitate the process of commercialization of agriculture. In this paper, empirical studies on marketed surplus of rice have been reviewed with a focus on the concepts and methods used, their strengths and weaknesses, and some recommendations have been made to improve estimation methodology in future studies.